Shared and Distinct Patterns of Oligodendroglial Response in α-Synucleinopathies and Tauopathies - Rohan, Zdenek; Milenkovic, Ivan; Lutz, Mirjam I; Matej, Radoslav; Kovacs, Gabor G (Journal of neuropathology and experimental neurology, 2016)
Pathological protein deposits in oligodendroglia are common but variable features of various neurodegenerative conditions. To evaluate oligodendrocyte response in neurodegenerative diseases (NDDs) with different extents of oligodendroglial protein deposition we performed immunostaining for tubulin polymerization-promoting protein p25α (TPPP/p25α), α-synuclein (α-syn), phospho-tau, ubiquitin, myelin basic protein, and the microglial marker HLA-DR. We investigated cases of multiple system atrophy ([MSA] n = 10), Lewy body disease ([LBD] n = 10), globular glial tauopathy ([GGT] n = 7) and progressive supranuclear palsy ([PSP] n = 10). Loss of nuclear TPPP/p25α immunoreactivity correlated significantly with the degree of microglial reaction and loss of myelin basic prtein density as a marker of tract degeneration. This was more prominent in MSA and GGT, which, together with enlarged cytoplasmic TPPP/p25α immunoreactivity and inclusion burden allowed these disorders to be grouped as predominant oligodendroglial proteinopathies. However, distinct features, ie more colocalization of α-syn than tau with TPPP/p25α, more obvious loss of oligodendrocyte density in MSA, but more prominent association of tau protein inclusions in GGT to loss of nuclear TPPP/p25α immunoreactivity, were also recognized. In addition, we observed previously underappreciated oligodendroglial α-synuclein pathology in the pallidothalamic tract in LBD. Our study demonstrates common and distinct aspects of oligodendroglial involvement in the pathogenesis of diverse NDDs.
Keywords: senioři; tau Proteins; proteiny tau; Progressive supranuclear palsy; senioři nad 80 let; Globular glial tauopathy; Middle Aged; mužské pohlaví; mozek; oligodendroglie; Nerve Tissue Proteins; Lewy body disease; Aged, 80 and over; Brain; ženské pohlaví; TPPP/p25α; Humans; Multiple system atrophy; Tauopathies; proteiny nervové tkáně; alpha-Synuclein; tauopatie; lidé středního věku; alfa-synuklein; neurodegenerativní nemoci; Oligodendroglia; Female; Aged; Neurodegenerative Diseases; lidé; Male